The role of chitotriosidase duplication gene polymorphism in the susceptibility to sarcoidosis - Maver, Aleš (Zdravniški vestnik, 2010)
Background: Sarcoidosis is a systemic granulomatous disease that most commonlyaffects respiratory system, and may present with an acute onset or follow a chronic course. Sarcoidosis has an established genetic component, supported by evidence from familial, population and linkage genetic studies. Several attempts at discerning the exact genetic background of sarcoidosis have produced mostly inconclusive results. Recently, the roles of fungal infection and exposure to fungal antigens have been implicated in sarcoidosis pathogenesis. A mammalian form of chitinolytic enzyme - chitotriosidase has been discovered, and it has been hypothesised to play a role in defense against chitin-containing pathogens and innate immunity. A 24 base pair duplication polymorphism in the chitotriosidase gene (CHIT1) has been described, causing abnormal mRNA splicing patterns, leading to enzymatically inactive chitotriosidase. Methods: An association study has been performed, comparing frequencies of duplication polymorphism in groups of 159 Slovenian patients with sarcoidosis and 272 healthy controls. Genotyping was performed by polymerase chain reaction (PCR), followed by size discrimination of PCR products with agarose gel electrophoresis. Statistical analyses have been performed using Pearsonćs Chi-Square test. Results: Our results did not show significant association of 24bp duplication polymorphism in CHIT1 gene with the susceptibility to sarcoidosis. Conclusions: In our study, we were unable to demonstrate a significant effect of duplication polymorphic variation in the CHIT1 gene on the susceptibility to sarcoidosis. However, other polymorphisms in CHIT1 gene should be investigated and additional studies performed in other genetically distinct populations.
Keywords: Chitin; etiologija; Genetics; genetika; Genotip; Genotype; Hitin; Polimerazna, verižna reakcija; polimorfizem; Polimorfizem (genetika); Polymerase Chain Reaction; Polymorphism (Genetics); Sarcoidosis; Sarkoidoza